Patients with History of Metastasis Have Differing Surgical Indications and Increased Perioperative Risk Following Revision Total Joint Arthroplasty - Aroob Zaheer BS; Alexander S. Vo BS; Guillermo Ramirez Campos BS; Nithin Gupta BS; Morgan Gable MD; Zachary Jodoin MD; Tyler K. Williamson DO; Frank A. Buttacavoli MD (Geriatric Orthopaedic Surgery & Rehabilitation)
Introduction Revision arthroplasty is an invasive procedure with increased morbidity relative to primary joint arthroplasty. Therefore, patients with metastatic cancer (Met) undergoing revision total joint arthroplasty (rTJA) may be at greater risk. This study assesses early postoperative outcomes among Met patients undergoing rTJA. Materials and Methods We reviewed the National Surgical Quality Improvement Program (NSQIP) database from 2015 to 2020 to evaluate rTHA/rTKA with Met and Non-Met. Univariate analysis and multivariate logistic regression were used to evaluate associations of Met patients compared with outcomes using odds ratio (OR) and 95% confidence interval (CI). Discriminatory accuracy was assessed using Receiver operating characteristic (ROC) curve and quantified using C-statistic. Results Adjusted analysis revealed Met patients undergoing rTKA were more likely to experience any complication (OR: 2.56, CI: [1.48–4.43]), major complication (OR: 2.17, CI: [1.24–3.82]), and mortality (OR: 7.99, CI: [2.70–23.65]). Met patients undergoing rTHA had higher associations with any complication (OR: 2.40, CI: [1.65–3.49]), major complication (OR: 2.19, CI: [1.47–3.25]), DVT (OR: 4.82, CI: [1.92–12.10]), and mortality (OR: 3.67, CI: [1.43–9.41]). Frailty had superior predictability of extended length of stay (C: 0.625 [0.619–0.630]) and mortality (C: 0.851 [0.824–0.880]). Conclusions Patients with metastatic cancer have elevated risk of complications after revision arthroplasty but may have moderate predictability by frailty assessment. Surgeons can utilize this information to emphasize protective strategies to mitigate risk during and following total joint arthroplasty. Level of Evidence III.